A Research on the Classification Validity of the Decisions Made According to Norm and Criterion-referenced Assessment Approaches*. (1st March 2016) - Ertoprak, Duygu Gizem; Dogan, Nuri
Abstract: In this study, the criterion-referenced assessment and norm-referenced assessment applications were examined comparatively to see whether the decisions made about the students led to any differences in their classification validity, and the results obtained were analyzed. For this purpose, the evaluation results belonging to the students were transferred into the passed/failed decisions in accordance with the rules in criterion and normreferenced assessment systems, and the obtained findings were analyzed with the discriminant analysis. The study was conducted with 1007 students from six universities who attended courses in the 2011-2012 academic year, and who had previously taken education (pedagogical formation) courses. At the end of the study, the classification validity of the decisions made about the students with the criterion-referenced assessment approach was seen to be higher. Thus, it can be said that making classification decisions about students using the criterion-referenced assessment approach can give more accurate results than the decisions made according to norm-referenced assessment approach.